PENERAPAN VIDEO EDUKASI LITERASI VISUAL MEMBACA DALAM BAHASA INDONESIA - Alexandra Azzahra Barus; Alifia Nur Fitri; Annisa Safitri; Devira Asni Syaputri; Hayat Alfarij Ihsan Purba; Khairun Nisa; Rizky Fadhilah; Mr. Lutfee Maroh; Lisa Septia Dewi Br Ginting (JOURNAL SAINS STUDENT RESEARCH, 2025)
Bahasa Indonesia is a learning program that focuses on developing knowledge, language skills, and positive attitudes towards the Indonesian language. Speaking skills are the ability to pronounce sounds, articulation or several words arranged into a sentence to express and convey thoughts, ideas, and feelings to the other person. The use of visual literacy-based learning media has become an increasingly important topic in education, especially in the context of learning Bahasa Indonesia. This article aims to present a comprehensive literature review on the influence of visual literacy-based biology learning media on improving student learning outcomes. The research method used is a literature review, by analyzing related studies and research, this article presents empirical evidence on the effectiveness of visual literacy-based learning media in improving student understanding and learning outcomes. Thus, the use of audio-visual media in the learning process can improve students' literacy skills and learning outcomes.